DEVELOPMENT OF STUDENTS' INTELLECTUAL QUALITIES AS A PEDAGOGICAL PROBLEM (American Journal of Pedagogical and Educational Research, 2024)
In the article, the development of intellectual qualities of students is a pedagogical problem; intellectual style, talent, intelligence are discussed, and it is aimed at clarifying the possibilities for developing the intellectual qualities of students.